2021
DOI: 10.2196/32127
|View full text |Cite
|
Sign up to set email alerts
|

Online Search Behavior Related to COVID-19 Vaccines: Infodemiology Study

Abstract: Background Vaccination against COVID-19 is an important public health strategy to address the ongoing pandemic. Examination of online search behavior related to COVID-19 vaccines can provide insights into the public's awareness, concerns, and interest regarding COVID-19 vaccination. Objective The aim of this study is to describe online search behavior related to COVID-19 vaccines during the start of public vaccination efforts in the United States. Methods… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 39 publications
2
20
0
Order By: Relevance
“…Many studies have applied this method to track trends in population attitudes toward COVID-19 vaccines based on data mining, as data mining can process long-term and large-scale data. Pullan et al [ 12 ] and An et al [ 13 ] analyzed data from Google Trends, and they both found that the number of searches related to COVID-19 vaccines had increased during the pandemic. Yin et al [ 14 ] proposed a novel behavioral dynamics model on Weibo messages to analyze vaccine acceptance in China, and they demonstrated that Chinese individuals were inclined to be positive about side effects over time.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have applied this method to track trends in population attitudes toward COVID-19 vaccines based on data mining, as data mining can process long-term and large-scale data. Pullan et al [ 12 ] and An et al [ 13 ] analyzed data from Google Trends, and they both found that the number of searches related to COVID-19 vaccines had increased during the pandemic. Yin et al [ 14 ] proposed a novel behavioral dynamics model on Weibo messages to analyze vaccine acceptance in China, and they demonstrated that Chinese individuals were inclined to be positive about side effects over time.…”
Section: Introductionmentioning
confidence: 99%
“…This work contributes to the growing literature on infodemiology , which seeks to employ search engine data in the service of health information seeking, forecasting, and surveillance [ 35 ]. Previous research has covered a wide variety of infectious diseases such as influenza [ 36 ], dengue [ 37 ], norovirus [ 38 ], COVID-19 [ 39 ], and sexually transmitted infections [ 40 ], as well as other topics like cancer [ 22 , 23 ], dementia [ 18 ], and mental health [ 20 ]. Among the limited literature exploring HIV/AIDS with internet search data, the methodology is often restricted to qualitative [ 41 ] or parametric methodology [ 42 ], with limited research on Africa.…”
Section: Discussionmentioning
confidence: 99%
“…A Twitter poll showed that more than half of the respondents were sceptical about COVID-19 vaccinations [ 16 ]. Another study, that examined online search behaviour related to COVID-19 vaccines during the beginning of public vaccination, found that many individuals who are uncertain about critical vaccine-related information do not engage in active online search to address their information needs, highlighting the importance of encouraging more active information-seeking, as well as a critical appraisal of health information on the web, as a strategy for combating misinformation about COVID-19 vaccines [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%